CONVENTIONAL AND UNCONVENTIONAL MONETARY POLICY. THE CASE OF ROMANIA - Plescau, Ioana (Studies and Scientific Researches. Economics Edition, 2016)
The aim of our paper is to analyze the conventional and unconventional monetary policy in Romania, in the context of the recent financial crisis. We study the relationship between interest rates and credit risk, but also the non-standard monetary measures that were adopted by the National Bank of Romania and their impact on the banking system. Our results point to a decrease of interest rates in the years after the crisis, which is in line with the majority of central banks that have reduced monetary rates in order to sustain the economy and the credit activity.